1988
DOI: 10.1111/j.1476-5381.1988.tb11752.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine releases endothelium‐derived hyperpolarizing factor and EDRF from rat blood vessels

Abstract: 1 The effects of haemoglobin and methylene blue on the acetylcholine (ACh)-induced electrical and mechanical responses of smooth muscle cells were investigated in rat aorta and rat main pulmonary artery.2 When the endothelium was intact, ACh induced a transient hyperpolarization and sustained relaxation of tissues precontracted with noradrenaline. Both hyperpolarization and relaxation were absent in preparations without endothelium. 3 Haemoglobin and methylene blue inhibited the ACh-induced relaxation, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
394
1
8

Year Published

1991
1991
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 637 publications
(417 citation statements)
references
References 29 publications
14
394
1
8
Order By: Relevance
“…Bolotina et al, (1994) also demonstrated that relaxation to NO was blocked by charybdotoxin, a speci®c inhibitor of calciumdependent potassium channels, in rabbit aortic smooth muscle cells. By contrast other studies reported that endotheliumdependent relaxation but not endothelium-dependent hyperpolarization was inhibited by methylene blue or Hb in rat (Chen et al, 1988) or rabbit arteries (Huang et al, 1988) indicating a factor other than NO caused hyperpolarization. Thus, both NO and EDHF have been suggested to open the potassium channels leading to hyperpolarization in response to ACh.…”
Section: Discussionmentioning
confidence: 46%
“…Bolotina et al, (1994) also demonstrated that relaxation to NO was blocked by charybdotoxin, a speci®c inhibitor of calciumdependent potassium channels, in rabbit aortic smooth muscle cells. By contrast other studies reported that endotheliumdependent relaxation but not endothelium-dependent hyperpolarization was inhibited by methylene blue or Hb in rat (Chen et al, 1988) or rabbit arteries (Huang et al, 1988) indicating a factor other than NO caused hyperpolarization. Thus, both NO and EDHF have been suggested to open the potassium channels leading to hyperpolarization in response to ACh.…”
Section: Discussionmentioning
confidence: 46%
“…Since Chen et al (1988) reported endothelium-dependent hyperpolarization of vascular smooth muscle, this phenomenon has been thought to be produced by an unidentified humoral substance (EDHF) released from vascular endothelium (Chen et al 1991). In the presence of 18â_glycyrrhetinic acid, electrical coupling between cells was effectively blocked and the membrane potential of individual cells could be well clamped while all cell types remained located within a multicellular preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In systemic arteries, the vascular endothelium plays a major role in the regulation of vasomotor tone through the release of the vasodilators, nitric oxide (Moncada et al, 1991), prostacyclin (Moncada & Vane, 1979) and the putative endotheliumderived hyperpolarizing factor (EDHF, Chen et al, 1988). There is now compelling evidence to support the view that endothelium-derived nitric oxide is an important mediator of vasomotor tone in the eye (for review see Koss, 1999).…”
Section: Introductionmentioning
confidence: 99%